Offshore recreational fisheries of large vulnerable sharks and teleost fish in the Mediterranean Sea: first information on the species caught - PANAYIOTOU, NIKOLAS; BITON PORSMOGUER SEBASTIΑN; MOUTOPOULOS DIMITRIOS Κ.; LLORET, JOSEP (Mediterranean Marine Science, 2020)
Large-sized pelagic sharks and teleost fish are vulnerable to overexploitation by professional fisheries but little is known about the species caught by recreational fishing. This study presents for the first time in the Mediterranean an evaluation of the catch of pelagic sharks and teleost fish being caught by recreational fishermen by analyzing publicly available videos posted on social media. The analysis reveals that several vulnerable species, including the blue shark Prionace glauca, the shortfin mako Isurus oxyrinchus, the thresher shark Alopias vulpinus, the sixgill shark Hexanchus griseus, the swordfish Xiphias gladius, and the Mediterranean spearfish Tetrapturus belone are caught by offshore recreational fishermen, with the blue shark and the swordfish being the most commonly caught species. The majority of individuals caught are juveniles that are mostly released back to sea, issues that are in agreement with field studies. New measures related to handling practices are proposed to protect these species.